2007
DOI: 10.1111/j.1365-2753.2007.00677.x
|View full text |Cite
|
Sign up to set email alerts
|

Accessing rural populations: role of the community pharmacist in a breast and cervical cancer screening programme

Abstract: Results suggest that the use of independent community pharmacies in the rural setting can be an effective method of recruiting women into public health programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…All ten studies reported outcome measures relating to the domain of behavioural determinants; increasing awareness and knowledge (n=7) [16-20, 24, 25]; recommending referral (n=3) [21][22][23]. Outcomes of four studies were identified as influencing patient's behavior [16,17,19,20]. Physiological and biochemical outcomes were measured in four studies (FOB n=2 [19,24], PSA n=1 [16], Pap/HPV DNA n=1 [21]) and health outcomes (cancer diagnosis) in two [16,19].…”
Section: Study Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…All ten studies reported outcome measures relating to the domain of behavioural determinants; increasing awareness and knowledge (n=7) [16-20, 24, 25]; recommending referral (n=3) [21][22][23]. Outcomes of four studies were identified as influencing patient's behavior [16,17,19,20]. Physiological and biochemical outcomes were measured in four studies (FOB n=2 [19,24], PSA n=1 [16], Pap/HPV DNA n=1 [21]) and health outcomes (cancer diagnosis) in two [16,19].…”
Section: Study Outcomesmentioning
confidence: 99%
“…Study locations were the US (n=5) [17][18][19][20]24], Australia (n=2) [22,23], Germany (n=1) [16], Italy (n=1) [21] and South Korea(n=1) [25]. The number of participants included in the studies ranged from 91 [23] to 14,041 [21], while the duration including follow up ranged from four weeks [19] to two years [16].…”
Section: Description Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations